Improving Mathematics Learning Outcome Through Outdoor Learning Based on Ethnomathematics of Bengkulu’s Traditional Game ‘Gotri Ayo Gotri - Yumiati, Yumiati; Haji, Saleh; Yulitasari, Eka (Universitas Muhammadiyah Mataram, 2023)
Many high school students have difficulty learning probability material. Meanwhile, probability is very important to be applied in everyday life, for example, in estimating and drawing conclusions based on the analysis of an experiment. Therefore, students' understanding of probabilities needs to be improved through learning that invites students to real situations. This study aims to improve the mathematics learning outcomes of probability topics (counting, permutations, combinations, and probabilities) through ethnomathematical outdoor learning based on the game 'Gotri Ayo Gotri (GAG)' for XII Class senior high school. The research method is a classroom action research with the following cycle stages: planning, action, reflection, and evaluation. The research subjects were 33 students (20 female students and 13 male students). The research instrument was a learning outcome test about the probability of as many as five items. Data were analyzed qualitatively. The results of the study are as follows: outdoor learning based on the ethnomathematics of the game 'Gotri Ayo Gotri (GAG)' can improve mathematics learning outcomes on probability topics with an average score of cycle 1 of 65.91, cycle 2 of 79.97, and cycle three score of 89.97. The novelty in this research is the form of the traditional Bengkulu GAG game. As an alternative to learning, it is recommended for high school mathematics teachers to apply traditional game-based learning outside the classroom to increase motivation and learning outcomes in mathematics.